REKOMENDASI PENEMBANGAN HOME INDUSTRY JAGUNG MARNING DESA BUKIT BARISAN KABUPATEN KEPAHIANG MELALUI ANALISIS PENDAPATAN - Lizvan Mangatur Sitorus; Herawansyah Herawansyah; Dodi Aprianto; Meko Gustian; Paisal Ansiska (Jurnal Media Ekonomi (JURMEK), 2021)
The businessmen is the home industry, the home industry is a small business that has an important role in the growth of the region and the country. The home industry is the backbone of the populist economic system aimed at reducing the problem of unemployment in society. Management of marning corn is one of the management of agricultural products. Corn is one of the important food commodities and is a priority for research and development centers and is a source of vitamins and minerals to fulfill needs. This study aims to determine the income of the marning corn home industry and at the same time provide recommendations for sustainable management in improving the quality and quantity of marning corn products in Bukit Barisan Village, Kepahiang Regency. The method used in this researc is the income analysis, SWOT, and QSPM. The result of this research is the income from each production process is Rp. 234.168,-. with a production cost of Rp. 557,832,-. The development of a home industry for marning corn in Bukit Barisan Village can be done by increasing the amount of production and expanding the market, increasing product quality, cooperation with agencies related to business development, product branding.